Broadband enhanced fluorescence using Zinc-Oxide nanoflower arrays - Wang,T; Costan,J; Centeno,A; Pang,J; Price,D; Ryan,M; Xie,F (Journal of Materials Chemistry C, 2015)
ZnO nanostructures were fabricated into flower-like nanoscale arrays by the hydrothermal growth of ZnO nanowires onto a self-assembled monolayer of polystyrene spheres on a glass substrate. Fluorescent molecules conjugated with streptavidin were incubated on glass with 3-(glycidoxypropyl) trimethoxysilane (GPTS) modified and biotinylated bovine serum albumin (bBSA) attached (GPTS–bBSA), aligned ZnO nanorod arrays and ZnO nanoflower arrays, respectively. An enhancement factor of up to 45 was obtained from ZnO nanoflower arrays, compared to less than 10 for the aligned nanorods. More importantly, using the same substrate, we observed a broadband fluorescence enhancement. The level of enhancement obtained from the nanoflower arrays is comparable with that from Metal Enhanced Fluorescence. The broadband nature of this process makes it an attractive alternative for fluorescent based device development.